Il bisogno di un tempo laterale. Del Giudice, Bazlen e «le storie di Ljuba» - Caritto, Manuel; Parodi, Jacopo (L’ospite ingrato, 2025)
This essay aims to present an absolutely unprecedented aspect of the texture of Daniele Del Giudice’s Wimbledon Stadium, 1983. It is an interview of the writer with Ljuba Blumenthal, the true love of Roberto (Bobi) Bazlen. This friend of Bazlen, the famous editorial consultant, shares her idea of the extravagant intellectual. How does this text conclude with the message of Del Giudice’s novel?